Personnel selection in the digital age: a review of validity and applicant reactions, and future research challenges. Issue 1 (2nd January 2020) - Woods, Stephen A.; Ahmed, Sara; Nikolaou, Ioannis; Costa, Ana Cristina; Anderson, Neil R.
ABSTRACT: We present a targeted review of recent developments and advances in digital selection procedures (DSPs) with particular attention to advances in internet-based techniques. By reviewing the emergence of DSPs in selection research and practice, we highlight five main categories of methods (online applications, online psychometric testing, digital interviews, gamified assessment and social media). We discuss the evidence base for each of these DSP groups, focusing on construct and criterion validity, and applicant reactions to their use in organizations. Based on the findings of our review, we present a critique of the evidence base for DSPs in industrial, work and organizational psychology and set out an agenda for advancing research. We identify pressing gaps in our understanding of DSPs, and ten key questions to be answered. Given that DSPs are likely to depart further from traditional non-digital selection procedures in the future, a theme in this agenda is the need to establish a distinct and specific literature on DSPs, and to do so at a pace that reflects the speed of the underlying technological advancement. In concluding, we, therefore, issue a call to action for selection researchers in work and organizational psychology to commence a new and rigorous multidisciplinary programme of scientific study of DSPs.